2015
DOI: 10.1515/cclm-2014-0387
|View full text |Cite
|
Sign up to set email alerts
|

Role of leptin in female reproduction

Abstract: Abstract:Reproductive function is dependent on energy resources. The role of weight, body composition, fat distribution and the effect of diet have been largely investigated in experimental female animals as well as in women. Any alteration in diet and/or weight may induce abnormalities in timing of sexual maturation and fertility. However, the cellular mechanisms involved in the fine coordination of energy balance and reproduction are largely unknown. The brain and hypothalamic structures receive endocrine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 150 publications
(199 reference statements)
3
84
1
3
Order By: Relevance
“…In addition, the satiety effect of leptin is also mediated by regulation of anorexigenic peptides such as POMC, cocaine-and amphetamineregulated transcript, neurotensin, corticotropin-releasing hormone and brain-derived neurotrophic factor (BDNF) (Golden et al 1997, Sahu 1998, Meister 2000, Liao et al 2012. Although the central effect of leptin has been well studied, accumulating studies show that leptin also plays an important role in directly regulating the function of peripheral organs like reproductive organs (Moschos et al 2002, Perez-Perez et al 2015. Leptin targets pancreatic β-cell to modulate glucose homeostasis through producing effects on β-cell mass and insulin expression and secretion (Marroqui et al 2012).…”
Section: Leptinmentioning
confidence: 99%
“…In addition, the satiety effect of leptin is also mediated by regulation of anorexigenic peptides such as POMC, cocaine-and amphetamineregulated transcript, neurotensin, corticotropin-releasing hormone and brain-derived neurotrophic factor (BDNF) (Golden et al 1997, Sahu 1998, Meister 2000, Liao et al 2012. Although the central effect of leptin has been well studied, accumulating studies show that leptin also plays an important role in directly regulating the function of peripheral organs like reproductive organs (Moschos et al 2002, Perez-Perez et al 2015. Leptin targets pancreatic β-cell to modulate glucose homeostasis through producing effects on β-cell mass and insulin expression and secretion (Marroqui et al 2012).…”
Section: Leptinmentioning
confidence: 99%
“…Leptin is a peptide hormone (16 kDa) that is primarily secreted by adipose tissue and acts as an essential regulator of body weight and energy metabolism (Friedman and Halaas 1998;Pérez-Pérez et al 2015). The plasma concentration of leptin is associated with the extent of obesity (Bouloumié et al 1998).…”
Section: Leptin Receptor Signaling and Atimentioning
confidence: 99%
“…The plasma concentration of leptin is associated with the extent of obesity (Bouloumié et al 1998). Biologically, leptin is regarded as a multifunctional hormone that is involved in various body functions such as hematopoiesis, osteogenesis, thermogenesis, angiogenesis, chondrogenesis, neuroendocrine processes, arterial pressure control, body weight homeostasis and immune functions (Fantuzzi and Faggioni 2000;Pérez-Pérez et al 2015;Sagawa et al 2002). The synthesis of leptin by various tissues and organs such as the pituitary, placenta, stomach, and skeletal muscle is consistent with its biological roles in these body systems (Reitman et al 2001).…”
Section: Leptin Receptor Signaling and Atimentioning
confidence: 99%
“…Leptin, a 16-kDa protein named OB, encoded by the obese (ob) gene, is secreted mainly by adipocytes. Although initially leptin was recognized as a crucial regulator of food intake, body fat mass and energy expenditure (Pelleymounter et al 1995) further studies revealed that this hormone is also implicated in the hypothalamic-pituitary regulation of the gonadotropin-gonadal axis, therefore it affects the reproductive processes (Chebab 2014, Perez-Perez et al 2015. The effect of leptin is mainly mediated via its functional receptor -the long isoform (OB-Rb).…”
Section: Introductionmentioning
confidence: 99%